Stadtgeographische Probleme des geteilten Berlin - Schöller, Peter (ERDKUNDE, 1953)
After heavy war damage, dismantling of industries and the loss of its function as capital, Berlin is also undergoing a thorough change of inner geographical structure as a consequence of the political division of the city and the isolation of West Berlin from its hinterland. The results of this disruption of inner structure of the metropolis, and of the political, economic and social changes in both parts of the city find geographical expression in various ways: such are shifts of the population, changes of industrial location, economic recrystallization, differentiation in the pattern of communications, dichotomy in architectural styles, City-Bildung, changes of urban foci, and finally redistribution and staffing alterations in urban services (zentrale Dienste). The consequences of the new political boundary have already produced effects which have indelibly marked the townscape. Nevertheless, no changes in its urban structure have yet taken place which would handicap a future reunification.